Effectiveness of Stress Management With Cognitive-Behavioral Approach on Cognitive Emotion Regulation in Mothers of Children With Cancer - Haji Seyed Javadi, Tahere; Hatami, Mohammad; Ahadi, Hasan; Kraskian, Adis (International Clinical Neuroscience Journal, 2019)
Background: The purpose of this study was to determine the effectiveness of stress management therapy with a cognitive-behavioral approach to cognitive emotion regulation in mothers of children with cancer. Methods: The research method was quasi-experimental with pre-test, post-test, and follow up design as well as the control group. The statistical population of this study included all mothers of children with cancer who referred to the Qods children’s hospital located in Qazvin province. A sample of 30 subjects was selected through purposive sampling and assigned to two groups of experimental (n = 15) and control (n = 15). Both groups were pre-tested using the Cognitive Emotion Regulation Questionnaire (CERQ). Then, the experimental group received 8 sessions of training in stress management skills with cognitive-behavioral approach while the control group did not receive any intervention. Subsequently, both groups administered post-test, and the data were analyzed by SPSS 21 software using single variable one-way ANOVA. Results: The results showed improvement in the scores of the experimental group mothers in cognitive emotion regulation variable and components of self-blame, acceptance, rumination, positive refocusing, refocus on planning, perspective-taking, catastrophization, and other-blame. However, no significant improvement observed in the component of positive reappraisal in parents of children with cancer (P < 0.01) and this maintained at the follow-up stage. Conclusion: Based on the findings of this study it can be concluded that teaching stress coping strategies with a cognitive-behavioral approach is an effective way to teach emotion regulation strategies to mothers of children with cancer suffering from emotional distress.